A model of algal organic carbon distributions in the Pearl River estuary using the amino acid carbon isotope values. (1st February 2021) - Kang, Peihong; Zhang, Han; Yang, Zixiang; Zhu, Yifan; He, Biyan; Li, Qing; Lee, Cindy; Tang, Tiantian
Abstract: To better understand the sources and behavior of estuarine labile organic matter, we measured stable carbon isotope patterns of individual amino acids in suspended particles and surface sediments from the Pearl River Estuary in China; samples were taken along a salinity transect in December, 2016. Here we demonstrate that carbon isotope values (δ 13 C) of individual amino acids in these samples gradually increase with salinity downstream, reflecting the increase in δ 13 C values of algal-derived organic carbon along the salinity gradient. The isotopic difference between amino acids and bulk organic carbon varies, most likely due to changes in the relative contributions of algal-derived organic matter and refractory terrestrial input. In addition, algal-derived organic matter can consist of labile and semi-labile organic matter in varied proportions depending on degradation state. This isotopic difference between amino acids and bulk organic carbon is much larger in surface sediments than in suspended particles, suggesting that labile organic carbon contributed more to suspended particles than to sediments. Using the relative abundances and δ 13 C ratios of amino acids and total organic carbon, a Lability Model was constructed to evaluate the relative contributions of three forms of estuarine organic carbon: labile algal material as amino acids, semi-labile algal material as lipids and acid-insoluble material, and refractory terrestrial organic material. The model suggests highly dynamic contributions of semi-labile algal-derived organic carbon and terrestrial organic carbon to estuarine particulate organic carbon. This evaluation of organic carbon sources illustrates the importance of decomposition in shaping the molecular composition and isotopic signature of particulate organic carbon in the estuary.